(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The article describes the content of Ibn al-Arabi’s concept of "Ayoni Sabita," which highlights the issues of knowledge, as well as the analysis of the concept of "Hazarothi hams."